2020
DOI: 10.1021/acsaem.0c00520
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic CoN-Decorated Pt Catalyst on Two-Dimensional Porous Co–N-Doped Carbon Nanosheet for Enhanced Oxygen Reduction Activity and Durability

Abstract: Herein, an oxygen reduction reaction (ORR) catalyst consisting of CoN-decorated Pt nanoparticles (NPs) on thin two-dimensional (2D) nanosheet-structured Co–N-doped porous carbon is prepared by utilizing the pyrolyzed nanosheet-shaped Co-based metal–organic framework as a template for Pt deposition. After Pt deposition and acid leaching, the remaining Co species on the Pt surface are converted to CoN species by ammonia heat treatment, which are also attached on the Pt surface. The as-synthesized CoN-decorated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…XPS of monometallic catalysts (N-Co, N-Ni, and N-Fe) were also performed to determine the relationship between structural features. 5b presents the high-resolution XPS spectrum of N 1s, showing the formation of four peaks centered at 397.8 eV for cyanide CN, 37 398.5 eV for pyridinic N, 399.0 eV for metal-nitrogen (M-N x ) bonding, and 400.0 eV for pyrrolic N. 38,39 The presence of M-N x species with a peak area of 34.6% indicates the bonding between the metal atoms and amino group via a coordination interaction. The O 1s peak of N-CoNiFe, located at approximately 530.9 eV was tted to metal-oxygen (M-O x ) bonding, C-O-C, and C]O/M-OH 40 (Fig.…”
Section: Morphological and Structural Characterizationmentioning
confidence: 99%
“…XPS of monometallic catalysts (N-Co, N-Ni, and N-Fe) were also performed to determine the relationship between structural features. 5b presents the high-resolution XPS spectrum of N 1s, showing the formation of four peaks centered at 397.8 eV for cyanide CN, 37 398.5 eV for pyridinic N, 399.0 eV for metal-nitrogen (M-N x ) bonding, and 400.0 eV for pyrrolic N. 38,39 The presence of M-N x species with a peak area of 34.6% indicates the bonding between the metal atoms and amino group via a coordination interaction. The O 1s peak of N-CoNiFe, located at approximately 530.9 eV was tted to metal-oxygen (M-O x ) bonding, C-O-C, and C]O/M-OH 40 (Fig.…”
Section: Morphological and Structural Characterizationmentioning
confidence: 99%
“…Previous studies indicated that Co NPs and Co-N x -C sites can significantly improve the ORR activity of Pt-based catalysts (see details in the Supporting Information). Therefore, the high ORR activity of Pt/Co@NC is attributed to the synergistic effects of Co nanoparticles, Pt NCs, and defective graphitic carbon matrix, which can offer abundant active sites and high electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Ru-based compounds are the most extensively studied cathode catalytic materials among transition metal chalcogenides, however, as a precious metal, Ru is not only scarce but expensive. In addition, Co-based transition metal chalcogenides are considered to be a potential material, unfortunately, it is difficult to meet requirements imposed on both high activity and good stability under the working conditions of a PEMFC (Tran et al, 2020;Zhong et al, 2020). Although non-metallic heteroatoms doped with carbon catalysts have certain advantages in terms of cost and performance, they fail to meet the requirements for commercialization (Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%